Longitudinal Analysis of Urine Metabolomics in Preterm Infants Based on UHPLC-MS/MS Technique - Sha Hong; Tianyi Liu; Xiyan Mu; Fujie Wen; Qian Shen; Yihui Zhai; Huiru Tang; Hong Xu (Discovery Medicine, 2026)
Background: The metabolic characteristics of preterm infants in the early postnatal period are closely linked to their growth and development. Investigating the corresponding metabolic changes that occur during the early postnatal maturation process of preterm infants may help improve their clinical management. In this prospective cohort study, we aimed to characterize urinary metabolism in preterm infants during the first two weeks of life and explore its relationship with metabolic homeostasis regulation in the early postnatal period.Methods: Between June 1, 2021, and October 1, 2022, 36 preterm infants eligible for enrollment were recruited from the Children’s Hospital of Fudan University (Shanghai, China), and urine samples were collected from these 36 preterm infants on postnatal day 1 (PND1), postnatal day 7 (PND7), and postnatal day 14 (PND14), respectively. A longitudinal urinary metabolomics study of preterm infants was conducted using an Ultra-high performance liquid chromatography-MS/MS (UHPLC-MS/MS) technique to compare urinary metabolic characteristics between PND7 and PND1 during the first postnatal week, and between PND14 and PND7 during the second postnatal week.Results: Broad-targeted urinary metabolomics analysis of preterm infants during the first week of life identified 75 differentially expressed urinary metabolites, of which 57 were upregulated compared to birth, while 18 were downregulated. The most significantly upregulated metabolite was L-3-hydroxykynurenine (p = 0.003), while the most significantly downregulated was N-Acetyltyrosine (p < 0.001). The metabolic pathway most significantly enriched among these 75 differentially expressed metabolites was the Arginine biosynthesis (p = 0.001). Compared to the first week, only 29 differentially expressed urinary metabolites were identified in preterm infants during the second week after birth, with 22 metabolites upregulated and 7 downregulated. Among them, (3-hydroxyphenyl)-3-hydroxypropionic acid (HPHPA) was the most significantly upregulated (p = 0.001), while N-Acetylhistidine was the most significantly downregulated (p = 0.008). The metabolic pathways most significantly enriched among these 29 urinary metabolites were Glycolysis/Gluconeogenesis (p = 0.008). Cinnamoylglycine, cyclic-3',5'-GMP and lactate were common urinary differentially expressed metabolites in the first and second weeks after birth in preterm infants, and the Glycolysis/Gluconeogenesis pathway was the metabolic pathway significantly associated with urinary differentially expressed metabolites in the first two weeks after birth.Conclusion: This single-center study describes the general characteristics of urinary metabolomics in preterm infants during the first two weeks after birth. Glycometabolism was identified as a key factor influencing changes in urine metabolism in preterm infants during the first two weeks after birth, providing a reference for metabolic adaptation assessment and clinical management strategies in the early postnatal period. Clinical Trial Registration: ClinicalTrials.gov (NCT06018831).